IMPLEMENTASI KEBIJAKAN LAYANAN KENAIKAN PANGKAT BERBASIS SIASN DI BADAN KEPEGAWAIAN DAERAH KABUPATEN SIDOARJO - Syarifatul Mufarrijah; Rosyidatuzzahro Anisykurlillah (Journal Publicuho, 2024)
The State Civil Apparatus Information System (SIASN) is a digital platform owned by the State Civil Service Agency that was developed to manage ASN personnel data and information in Indonesia. One of the services available in SIASN is the promotion service. This study aims to find out the implementation of the SIASN-Based Promotion Service Policy in the Regional Civil Service Agency of Sidoarjo Regency, which is based on Regulation of the State Civil Service Agency Number 7 of 2023 concerning the State Civil Apparatus Information System (SIASN) and a circular letter from BKN concerning the acceleration of ASN-based promotion and mutation services based on SIASN. The research method used is qualitative research, using primary and secondary data sources, and refers to Edward III's theory. Data collection techniques are carried out in three ways: through interviews, observations, and literature studies. The results of the research conducted show that the implementation of the SIASN-based promotion service policy in the BKD of the Sidoarjo district is quite optimal because the presence of SIASN can cut the bureaucratic flow. However, there are obstacles that are still faced today, namely weak validity/updating data and minimal awareness of ASN